The Influence of PAI Learning, Parental Social Support, and Peer Quality on Prosocial Attitudes of Junior High School Students in Malang City - Cahayaningsih, Ica Putri; Wahidmurni, Wahidmurni; Wahyuni, Esa Nur (Pendidikan Agama Islam STIT Palapa Nusantara, 2025)
This study investigates the factors influencing prosocial attitudes among junior high school students, focusing on Islamic Religious Education (PAI) learning, parental social support, and peer quality. The research aims to analyze the effects of these variables on students’ prosocial behavior and to examine the moderating role of peer quality. Employing a quantitative correlational design, the study involved 155 randomly selected eighth-grade students from three schools in Malang City (SMPN 12 Malang, SMP Lab UM, and MTs Muhammadiyah 1 Malang). Data were collected via a validated and reliable Likert-scale questionnaire and analyzed using multiple linear regression and moderated regression analysis (MRA). Results indicate that both PAI learning and parental social support significantly influence prosocial attitudes (p < 0.001 and p = 0.011, respectively), whereas peer quality did not demonstrate a significant moderating effect (p > 0.05). These findings suggest that the internalization of PAI values and supportive parenting are primary determinants of prosocial behavior, independent of peer relationship quality. The study concludes that educational and familial environments serve as crucial foundations for fostering prosocial attitudes, with peer interactions providing supplementary support. Practically, schools are encouraged to enhance contextualized and applicative PAI instruction, while parents should strengthen emotional and instrumental support. This research contributes to developing an integrative character education model that bridges school, family, and social environments.